FACTORS AIMED AT DEVELOPING COMPETENCIES IN PHYSICS EDUCATION - N.Z.Mamadaliyeva, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  intensive  work  on  improving  physics  education,  the  goals  and objectives of physics teaching are presented.